Evaluation of the HIrisPlex-S system in a Brazilian population sample - Carratto, T. M.T.; Marcorin, L.; Debortoli, G.; Silva, G. V.; Fracasso, N. C.A.; Oliveira, M. L.G.; Pereira, A. L.E.; Silva, A. B.C.; Donadi, E. A.; Simões, A. L.; Castelli, E. C. [UNESP]; Norton, H. L.; et al. (Elsevier, 2019)
The main goal of DNA phenotyping is to predict externally visible characteristics (EVCs) of an individual using only its genetic information. Nowadays, the HIrisPlex-S system stands as a reliable model designed for skin color prediction. However, prediction of skin color phenotypes has not been thoroughly tested in recently admixed populations, so it is important to evaluate the applicability of this tool in these populations. This study aims to analyze the HIrisPlex-S system accuracy in an admixed sample of 276 individuals from the region of Ribeirão Preto city in Southeastern Brazil. Predictive markers were directly genotyped by Next-Generation Sequencing (NGS), Infinium Multi-Ethnic Global-8 (MEGA) Kit Array (Illumina), or imputed using the IMPUTE2 software. Skin color predictions were performed using the HIrisPlex-S online tool. Our report shows that, except for dark to black color, the tool consistently fails in determining skin phenotypes. Therefore, results reveal that the HIrisPlex-S System is less reliable when dealing with admixed population samples, not supporting its utility for forensic casework in Brazil.
Keywords: DNA array; DNA phenotyping; Next-generation sequencing